2022
DOI: 10.4254/wjh.v14.i1.140
|View full text |Cite
|
Sign up to set email alerts
|

Targets of immunotherapy for hepatocellular carcinoma: An update

Abstract: Hepatocellular carcinoma, the most common primary liver cancer, in an immunogenic tumor with a poor prognosis because these tumors are diagnosed at late stages. Although, surgical resection, ablation, liver transplant, and locoregional therapies are available for early stages; however, there are yet no effective treatment for advanced and recurrent tumors. Immune checkpoint inhibitor therapy and adoptive cell transfer therapy has gained the popularity with some positive results because these therapies overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 83 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…Further studies will help to establish whether ICB administration actively induces TLS formation, and if B lymphocytes and TLS creation have an active and beneficial role in immunotherapy response. In this way, clinical strategies based on drugs that modulate B lymphocytes or TLS formation have been studied extensively to fight solid tumors [ 102 , 106 , 107 ].…”
Section: Clinical Application and Future Perspective Of B Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies will help to establish whether ICB administration actively induces TLS formation, and if B lymphocytes and TLS creation have an active and beneficial role in immunotherapy response. In this way, clinical strategies based on drugs that modulate B lymphocytes or TLS formation have been studied extensively to fight solid tumors [ 102 , 106 , 107 ].…”
Section: Clinical Application and Future Perspective Of B Lymphocytesmentioning
confidence: 99%
“…Current studies have demonstrated a marked heterogeneity in HCC tumors and highlighted that the crosstalk between cancer cells and the liver microenvironment promotes tumorigenesis and HCC pathogenesis, by pushing cell proliferation, survival, and the ability of migration and evasion [ 108 ]. In detail, the TME in HCC appears to be immunosuppressive, promoting the proliferation, invasion, and metastasis of tumors [ 106 , 107 ]. Thus, a better characterization of the immune landscape of HCC at high resolution would facilitate refining patient stratification and identify putative immune-therapeutic targets in order to develop novel therapies for HCC.…”
Section: Effect Of B Cells On Primary Liver Tumorsmentioning
confidence: 99%
“…These findings suggest that the impact of PEG-IFN-α on improving liver function and inhibiting disease progression during HBV infection is closely related to the CLST-aCD4 axis, which requires further experimental verification. HCC is resistant to current therapies (Song et al, 2021;Rai and Mukherjee, 2022;Xia et al, 2022;Zhang et al, 2022), and a novel strategy that considers the immunology of the disease to improve treatment remains important (Donne and Lujambio, 2022;Rai and Mukherjee, 2022;Shen et al, 2022). Significant differences in sorafenib response between the CLST high aCD4 high and CLST low aCD4 low subgroups illustrated that CLST and aCD4 might be important biomarkers for optimizing the use of multi-kinase inhibitors for precision HCC treatment.…”
Section: Figurementioning
confidence: 99%
“…Although TACE combined with MWA treatment can enhance the therapeutic effect of large hepatocellular carcinoma [3] [4], the synergistic action of anti-angiogenic targeted agents and immunotherapy drugs has significant advantages. By changing the Tumormicro-Environment (TME) [5], necrotic tumor cells after chemoembolization form new tumor-associated antigens to modulate the body's immune positivity. The anti-angiogenic targeted agents can prevent the reconstruction and regeneration of tumor vessels, and avoid the compensatory increase of Vascular Endothelial Growth Factor (VEGF) in a hypoxic environment after TACE [6].…”
Section: Introductionmentioning
confidence: 99%